Teaching English through Movies: Practical Aspect (with the Reference to «The Crown»). Part 1 - Hlavatska, Yuliia (Pedagogical Discourse, 2025)
This paper highlights some practical aspects of teaching English through movies. Its relevance is that learning English through films contributes to developing communicative competence, that is, the ability to communicate effectively in real situations. Moreover, it enhances non-linguistic students’ motivation and engagement in the educational process. This paper continues to focus on two aspects of methodological work using scenes from the series «The Crown»: communicative and lexical. We aim to present the methodological principles for integrating cinematic discourse into the teaching process while emphasising the importance of conversation. The case study examines a scene from «The Crown» by Peter Morgan, featuring the first meeting between Lady Diana Spencer and Prince Charles. Various scientific methods have been utilised to meet this paper’s objectives and address the assigned tasks. They include analysis and synthesis, as well as concretisation and generalisation. Additionally, didactic methods such as preparation for understanding, explanation of new material, reinforcement, and questioning have been incorporated. This paper is organised as follows: 1) exploring why «The Crown» is a valuable resource for students learning English; 2) describing the Queen’s accent; 3) providing brief information about two globally recognised personalities and two main characters in «The Crown» – Princess Diana and Prince Charles – from a communicative perspective; 4) understanding new vocabulary through brainstorming lexical units within the lexical aspect. As summarized, the dialogue in the show features a rich blend of formal and informal language, allowing students to broaden their vocabulary effectively; the series deepens students’ understanding of the context behind idiomatic expressions, making the language more relatable and practical; it enhances listening skills and helps students grasp different English pronunciations, fostering better communication; watching the show with English subtitles improves comprehension of the spoken dialogue; the engaging storytelling keeps viewers interested, maintaining motivation and making the learning process enjoyable and rewarding.